Peranan Orang Tua dalam Menumbuhkan Pemahaman pada Anak Mengenai Pentingnya Ibadah Shalat Berjamaah - Ditya Fatinia; Ajat Rukajat; Khalid Ramdhani (AS-SABIQUN, 2022)
This analysis leads to the role of parents in fostering children's understanding of the importance of congregational prayer services and factors that support and hinder parents in carrying out their role to foster an understanding of the importance of congregational prayer services to children. The method used in this study is a qualitative method with a descriptive approach. The subjects of the study in this analysis are parents and children. The data collection techniques used are observation and interviews. The results of this study prove that congregational prayer services are mandatory for all Muslims without exception, the role of parents in fostering understanding in children about the importance of congregational prayer services is carried out by providing the best possible understanding and explanation, providing reflection examples in carrying out congregational prayer services, and providing reprimands and warnings. Supporting factors are the role of parents, the environment of the place of residence, friendships, and worship facilities. Meanwhile, the factor that hinders it is the lack of enthusiasm and interest of children in the excessive use of electronic media such as cellphones and televisions.